Novel class of photochromic molecules exhibiting photo-switching in the solid state - Loan, Thomas; Santra, Mithun; Bradley, Mark (Frontiers in Chemistry, 2023)
Photo-switching compounds are widely used as super-resolution imaging agents, anti-counterfeiting dyes, and molecules that are able to control drug–receptor interactions. However, advancement of this field has been limited by the number of classes of molecules that exhibit this phenomenon, and thus there are growing activities to discover new photo-switching compounds that diversify and improve current applications and include the so-called donor–acceptor Stenhouse adducts. Herein, a new class of compounds, phenylindole alkene dimers, are presented as a novel class of photochromic molecules that exhibit photo-switching in the solid state. The synthesis of a small library of these compounds allowed the tuning of their optical properties. Surfaces coated with these photo-switches can be used as writable materials in a variety of applications.